Parallel algorithms - Casanova, Henri; Legrand, Arnaud; Robert, Yves, 1938- (Boca Raton, FL : CRC Press, 2009)
Focusing on algorithms for distributed-memory parallel architectures, this book covers theoretical models of parallel computation, parallel algorithm design for homogeneous and heterogeneous platforms, complexity and performance analysis, and essential notions of scheduling.
Preface Models PRAM Model Pointer Jumping Performance Evaluation of PRAM Algorithms Comparison of PRAM Models Sorting Machine Relevance of the PRAM Model Sorting Networks Odd-Even Merge Sort Sorting on a One-Dimensional Network Networking Interconnection Networks Communication Model Case Study: The Unidirectional Ring Case Study: The Hypercube Peer-to-Peer Computing Parallel Algorithms Algorithms on a Ring of Processors Matrix-Vector Multiplication Matrix-Matrix Multiplication A First Look at Stencil Applications LU Factorization A Second Look at Stencil Applications Implementing Logical Topologies Distributed vs. Centralized Implementations Summary of Algorithmic Principles Algorithms on Grids of Processors Logical Two-Dimensional Grid Topologies Communication on a Grid of Processors Matrix Multiplication on a Grid of Processors Two-Dimensional Block Cyclic Data Distribution Load Balancing on Heterogeneous Platforms Load Balancing for One-Dimensional Data Distributions Load Balancing for Two-Dimensional Data Distributions Free Two-Dimensional Partitioning on a Heterogeneous Grid Scheduling Scheduling Introduction Scheduling Task Graphs Solving Pb(â ) Solving Pb(p) Taking Communication Costs into Account Pb(â ) with Communications List Heuristics for Pb(p) with Communications Extension to Heterogeneous Platforms Advanced Scheduling Divisible Load Scheduling Steady-State Scheduling Workflow Scheduling Hyperplane Scheduling (or Scheduling at Compile-Time) Bibliography Index Exercises and Answers appear at the end of each chapter.
"A Chapman & Hall book."
Includes bibliographical references (pages 323-332) and index.
CSE
Karim International
Keywords: Parallel algorithms; Parallel programming (Computer science).; Computer science